Hubungan antara Sikap ibu Tentang Peran Gender dengan Pilihan Anak pada Kegiatan Bermain - Sri Maryatim, Arundati Shinta, dan Bimon (Jurnal Psikologi, 2012)
Objective of this research is to explain the prediction of mother's gender role attitude on children’s gendered playing activity. High gender stereotype attitude on mothers will predict the gender stereotype choice on playing activity among children. There were 115 children aged 6-7 years old. first grade from 4 public elementary schools in Yogyakarta participated in this research. Part of the OAT-AM (Occupation. Activity, Trait - Attitude Measure) Scale was utilized to measure mother's gender role attitude. Measuring children's gendered choice on playing activity was utilizing the Children’s Playing Activity Scale, and the 18 picture items (8 were feminine items. 8 were masculine items, and 2 were neutral items) were obtained from several children books. Result of the simple regression analysis was F (1, 108) = 1.149, p >.05, non significant. It was revealed that mother's gender role attitude could not predict children's gendered choice on playing activity. Several recommendations related the research variables were discussed.